Food waste composting and their association with seed germination on kale seed - Nurul Syafiqkha Abdul Manaf,; Nurhidayah Hamzah,; Siti Nurulhuda Mohd Imran,; Nur Syahiza Zainuddin,; Irma Noorazurah Mohamed,; Marfiah Ab Wahid,; Zulhailmy Mohd Yatim,; Mohd Zuraidi Komari, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Food waste has an influence throughout the whole food supply chain, from production to consumption. Composting effectively and affordably reduces the need for synthetic fertilizers, water, soil erosion, pesticides, and soil carbon storage. Composting may also improve crop yields and soil fertility, leading to more sustainable farming practices. The potential of efficient microorganisms (EM) for dehydrated food waste decomposition was investigated in this study. The research assessed the temperature and pH profiles during composting, whereas nitrogen, phosphorus, potassium, organic content, and E. coli were measured in mature composts. Therefore, the study revealed that EM greatly hastened the composting process by boosting critical factors such as temperature, pH, nitrogen content (TN : 1.17±0.6%, TP: 0.059±1.92%, K: 0.12±5.3%) organic enrichment (85%), and E-coli (<1 MPN/g). The germination index (GI) of kale seed was then analysed with the study’s findings indicating an 80% soil-compost ratio was the best. This research investigates the use of effective microorganisms (EM) to transform food waste into beneficial agricultural resources, with favourable results for soil health and kale seed germination. Researchers and circular economy officials may use the results to promote sustainable agriculture. The research helps to minimize landfill food waste, methane emissions, and synthetic fertilizer consumption, all of which benefit the environment. Farmers and gardeners may use the findings to boost soil fertility and crop yields on a budget. This research indicates that food waste may be transformed into useful resources, encouraging sustainable and eco-friendly agricultural